Novel pharmaceutical co-crystals of gefitinib: synthesis, dissolution, cytotoxicity, and theoretical studies. Issue 17 (11th April 2023) - Shaik, Althaf; Bhagwat, Pranav Umesh; Palanisamy, Parimaladevi; Chhabria, Dimple; Dubey, Pankaj; Kirubakaran, Sivapriya; Thiruvenkatam, Vijay
Abstract : Crystal engineering of gefitinib by forming cocrystals help in modulating its physico-chemical properties while retaining its biological activity. Abstract : Gefitinib (GEF) is an ATP-competitive inhibitor used in the treatment of advanced non-small cell lung cancer. However, the pharmaceutical efficacy of this drug is currently limited due to poor aqueous solubility (2.55 μg mL −1 ). Therefore, we engineered three co-crystals of GEF with suitable coformers like cinnamic acid (CA), sorbic acid (SA) and resorcinol (RES). Solvent assisted grinding combined with slow evaporation of solvent resulted in three co-crystals. Structural elucidation of the crystals revealed that GEF formed a 1 : 1 co-crystal with CA (GCA), while it formed a 1 : 1 : 1 co-crystal hydrate with RES (GRES·H2 O) and SA (GSA·H2 O). Further, dissolution studies showed that there is an increase in the solubility of the cocrystal GCA. The synthesized co-crystals showed a comparable potency with respect to GEF in a cell viability assay. In addition, we quantified various intermolecular interactions in the co-crystals of GEF using Hirshfeld surface and 2D fingerprint plot analysis. The improvement in solubility along with the comparable efficacy of co-crystals cement the importance of pharmaceutical cocrystals in improving the physico-chemical properties of drug molecules.